LC₅₀ Toxicity Activity Test Of Ethanol Extract Of Cardamom Leaves (Amomum cardamomum L.) On Shrimp Larvae (Artemia salina L) Using Brine Shrimp Lethality Test (BSLT) Method - Suharyanisa Suharyanisa; Betharina Br Tarigan; Yanti Musyawarah; Jhon Manrius Laia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
There are many negative effects on the use of chemical-based medicine, therefore many researchers are interested in finding natural ingredients that have the potential to replace chemical treatment. One of the plants from the Zingiberaceae family that is used as a medicinal ingredient is cardamom plant (Amomum cardamomun L), Many people often use cardamom for treatment such as aromatic ingredients, carminative (reducing gas in the stomach), cough medicine, halitosis and so on. Cardamom contains phytochemical compounds such as alkaloids, flavonoids, tannins, and saponins. The purpose of this study was to analyze the level of bioactivity of cardamom leaf ethanol extract to Artemia salina L shrimp larvae by BSLT method and determine the LC₅₀ value. This study used quantitative methods that were experimental and used 6 treatment concentrations, namely 25 ppm, 50 ppm, 100 ppm, 200 ppm, 500 ppm, 1000 ppm and 1 negative control with each concentration replicated 5 times. Artemia salina L larvae were used as many as 350 heads with 10 heads each for each concentration. The death of larvae is calculated after 24 hours of treatment. The calculation result of LC₅₀ from cardamom leaf ethanol extract (Amomum cardamomum L) with data analysis using SPSS version 25 is 151,671 ppm. This shows that cardamom leaf ethanol extract (Amomum cardamomum L) is toxic due to LC₅₀